Analysis of the success level of the Independent Campus Competition Program (PK-KM) on the quality of higher education in higher education in Universitas 17 Agustus 1945 Surabaya - Murnawan, Hery; Wati, Putu Eka Dewi Karunia; Saves, Faradlillah; Michael, Tomy; Kisworo, Dimas Andrianto; Sari, Amelia Puspita (Technium Social Sciences Journal, 2022)
The internship program is able to improve students’ soft skills and hard skills as well as solve problems that exist in the industrial world. The student exchange program is able to improve student competence in participating in the transfer of existing knowledge at partner universities. Student certification and training programs are able to improve student scientific discipline in identifying problems and solving problems according to the scientific field. The Thematic Real Work Lecture Program is able to understand the culture, social and economics of the community so that students have the ability to draft village regulations and socialize them. Students’ abilities in internships, student exchanges, student certification and training, and thematic Real Work Lecture activities are expected to enable students to achieve KPI 1, namely Graduates Get Decent Work.